Padina boergesenii mediated synthesis of Se-ZnO bimetallic nanoparticles for effective anticancer activity - Thirupathi, Balaji; Pongen, Yimtar Lanutoshi; Kaveriyappan, Govindarajan Rasiravathanahalli; Dara, Pavan Kumar; Rathinasamy, Suresh; Vinayagam, Saranya; Sundaram, Thanigaivel; Hyun, Baek Kwang; Durairaj, Thirumurugan; Sekar, Suresh Kumar Rajamani (Frontiers in Microbiology, 2024)
Introduction Evaluating the anticancer property of Padina boergesenii mediated bimetallic nanoparticles. Methods The present study focuses on synthesizing Se-ZnO bimetallic nanoparticles from an aqueous algal extract of brown algae Padina boergesenii.Synthesized Se-ZnO NPs were characterized by UV, FTIR, SEM-EDS and HRTEM for confirmation along with the anticancer activity by MTT assay. Results The UV gave an absorbance peak at 342 and 370 nm, and the FTIR showed functional groups involved in synthesizing Se-ZnO NPs. The TEM micrographs indicated the crystalline nature and confirmed the size of the Se-ZnO NPs to be at an average size of 26.14 nm. Anticancer efficacy against the MCF-7 breast and HepG2 (hepatoblastoma) cell lines were also demonstrated, attaining an IC50 value of 67.9 µg and 74.9 µg/ml respectively, which caused 50% cell death. Discussion This work aims to highlight an effective method for delivering bioactive compounds extracted from brown algae and emphasize its future therapeutic prospects. The potential of Selenium-Zinc oxide nanoparticles is of great interest due to the biocompatibility and low toxicity aspects of selenium combined with the cost-effectiveness and sustainability of zinc metal. The presence of bioactive compounds contributed to the stability of the nanoparticles and acted as capping properties.